2021
DOI: 10.1155/2021/5963868
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Prognostic Value Exploration of Radiotherapy Sensitivity-Associated Genes in Non-Small-Cell Lung Cancer

Abstract: Background. Non-small-cell lung cancer (NSCLC) is a prevalent malignancy with high mortality and poor prognosis. The radiotherapy is one of the most common treatments of NSCLC, and the radiotherapy sensitivity of patients could affect the individual prognosis of NSCLC. However, the prognostic signatures related to radiotherapy response still remain limited. Here, we explored the radiosensitivity-associated genes and constructed the prognostically predictive model of NSCLC cases. Methods. The NSCLC samples with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In order to better understand the differences between different subtypes, we used WGCNA analysis to identify hub genes among each subtype. Extensive analyses showed that WGCNA was an effective method for identifying phenotype-genotype linkages and biomarkers and therapeutic targets ( Niemira et al, 2019 ; Ma et al, 2021 ; Zhang et al, 2022 ). Nine modules were obtained, and pink module was highly associated with Stromal-E subtype.…”
Section: Discussionmentioning
confidence: 99%
“…In order to better understand the differences between different subtypes, we used WGCNA analysis to identify hub genes among each subtype. Extensive analyses showed that WGCNA was an effective method for identifying phenotype-genotype linkages and biomarkers and therapeutic targets ( Niemira et al, 2019 ; Ma et al, 2021 ; Zhang et al, 2022 ). Nine modules were obtained, and pink module was highly associated with Stromal-E subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is one of the most common treatments for NSCLC, and the tumor sensitivity to radiotherapy may affect individual prognoses of NSCLC. However, predictable signatures related to the radiotherapy response are still limited [ 31 ]. The importance of upregulation, enhanced activation, and critical signature of the PI3K/Akt/mTOR pathway are well documented.…”
Section: Molecular Radioresistance Mechanismsmentioning
confidence: 99%
“…A large number of regularization regression models (e.g. LASSO regression) have been demonstrated to be effective [9][10][11][12][13][14]. Other genebased machine-learning algorithms such as random forest, partial least squares, and SVM could also successfully predict radiosensitivity and radiocurability [15,16].…”
Section: Introductionmentioning
confidence: 99%